2019
DOI: 10.1016/j.infpip.2019.100025
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Antibiotic Stewardship Programs - Qualitative analysis of numerous hospitals in a developing country

Abstract: Summary Antimicrobial stewardship programs (ASP) are an essential practice to prevent increasing resistance against antibiotics. A successful ASP monitors not only prescribing patterns and practices but also contributes in minimizing the toxic effects of antibiotics. Moreover, ASP also facilitates the selection of disease specific antibiotics and enforces rules and regulations to rationalize the use of antibiotics. The aim of the study is to highlight the core elements of Hospital Antibiotic Steward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Our research was in concordance with other study, which recommended monitoring the reduction in resistance and the reduction in infection rate; however, they also included the calculation of the lowered cost by applying ASP [15]. In another study performed for hospitals in Karashi, several items like switching from IV to oral route, dose adjustments in organ dysfunction, dose optimization based on Pharmacokinetics/Pharmacodynamics data in treatment of resistant organisms [23]. Also in a practical toolkit issued by WHO for antimicrobial stewardship in low & middle income countries, many items were included in the monitoring and surveillance section.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our research was in concordance with other study, which recommended monitoring the reduction in resistance and the reduction in infection rate; however, they also included the calculation of the lowered cost by applying ASP [15]. In another study performed for hospitals in Karashi, several items like switching from IV to oral route, dose adjustments in organ dysfunction, dose optimization based on Pharmacokinetics/Pharmacodynamics data in treatment of resistant organisms [23]. Also in a practical toolkit issued by WHO for antimicrobial stewardship in low & middle income countries, many items were included in the monitoring and surveillance section.…”
Section: Discussionsupporting
confidence: 82%
“…Mushtaque et al reported 36 % of hospitals produce a cumulative antibiotic susceptibility report based on national guidelines and local susceptibility patterns. He also mentioned that optimizing doses through pharmacokinetics/pharmacodynamics principles, was performed by 68% of the hospitals, in the treatment of organisms with reduced susceptibility [23].…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned study had participating physicians mainly from the public hospitals, while our study included physicians (MS/AMS/DMS) and pharmacists from both private and public sector hospitals in proportion in 2020. Another study conducted in Karachi, a city in the province of Sindh, Pakistan, identified similar gaps in practice of antibiotic stewardship in hospitals [ 24 ]. This study reported a serious lack of leadership commitment and reporting antibiotic use in the 44 hospitals that participated, which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%